The scarlet slipper mystery - Keene, Carolyn (New York Grosset & Dunlap, 1974)
Nancy Drew comes to the aid of the owners of a local dancing school when they receive an anonymous note threatening their lives.
Keywords: Smuggling -- Fiction; Mystery and detective stories